Bulk density and water capacity analysis at magot compost and at soil containing pumice on Lombok Island - Fathoni, Ahmad; Suhairin, Suhairin; Wahyuni, Ida; Muliatiningsih, Muliatiningsih (Universitas Muhammadiyah Mataram, 2023)
Mineral soil has a high bulk density and is a limiting factor as a nursery medium. For the application of nursery media, planting media that is light, large water holding capacity are also needed. The magot compost comes from the Magot Lingsar unit the Regional TPA of NTB Province and the soil contains pumice an average of 68.2% comes from Tanak Beak Village, Central Lombok Regency, which has potential as a medium for nurseries. The purpose of this study was to identify the Bulk Density and water holding capacity of magot compost and soil containing pumice with the control variable of mineral soil from Labuapi, West Lombok Regency. Bulk density analysis method by analyzing dry weight per unit volume on soil rings and water capacity by analyzing wet weight minus dry weight. The subjects studied were magot compost with size < 2 mm, soil containing pumice size < 2 mm and control soil mineral rice fields. The results showed that the lowest Bulk Density was magot compost 0.42 gr/cm3, soil containing soil 0,64 gr/cm3, and rice field soil 1.42 gr/cm3, this was because magot compost was residue from waste. While the largest water holding capacity was soil containing pumice of 42.67%, magot compost 22.00%, and paddy soil 6.33%, caused by the number of macro and micro pores in pumice, whereas in magot compost water is bound to the humus surface. Suggestions for further research are the permanent wilting point time test on plant seeds.